2009
DOI: 10.3168/jds.2008-1577
|View full text |Cite
|
Sign up to set email alerts
|

Long-term performance of visual and electronic identification devices in dairy goats

Abstract: Dairy goat kids born during a 3-yr period (n = 97) and their mothers (n = 29) were used for a long-term evaluation of the performance of 9 types of identification (ID) devices. Kids wore multiple ID devices: visual ear tags (V1, tip-tag, n = 47; V2, official, n = 50), electronic ear tags (E1, button-button, n = 46; E2, flag-button, n = 46), electronic rumen boluses (B1, mini-bolus 14 g, n = 92; B2, mini-bolus 20 g, n = 28; B3, standard bolus 75 g, n = 34) and glass-encapsulated transponders injected in the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(58 citation statements)
references
References 16 publications
6
49
1
2
Order By: Relevance
“…Infections occurred in the form of ear swelling, irritation under the ear tags, inflammation, and feelings of discomfort or pain when touched. The num- ber of infected ears caused by metal-tipped ear tags is similar to the value of 3.3 % reported by Carne et al (2009). On the other hand, this value is lower than the 7.4 % average value reported by Thomas et al (2006) for five different types of electronic ear tags in ewes, the 80 and 50 % values reported by Karakuş et al (2015b), respectively, for electronic and official plastic ear tags (metal-tipped) in lambs, and the 17.6 and 45.9 % infected ear values also reported by Karakuş et al (2016) for, respectively, metal-tipped and electronic ear tags in goat kids.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Infections occurred in the form of ear swelling, irritation under the ear tags, inflammation, and feelings of discomfort or pain when touched. The num- ber of infected ears caused by metal-tipped ear tags is similar to the value of 3.3 % reported by Carne et al (2009). On the other hand, this value is lower than the 7.4 % average value reported by Thomas et al (2006) for five different types of electronic ear tags in ewes, the 80 and 50 % values reported by Karakuş et al (2015b), respectively, for electronic and official plastic ear tags (metal-tipped) in lambs, and the 17.6 and 45.9 % infected ear values also reported by Karakuş et al (2016) for, respectively, metal-tipped and electronic ear tags in goat kids.…”
Section: Discussionsupporting
confidence: 74%
“…In contrast, 8 out of 60 lambs with e-ET (13.3 %) had infections. The number of infected ears caused by e-ET is higher than that reported by Thomas et al (2006) and Carne et al (2009) but lower than that reported by Karakuş et al (2015bKarakuş et al ( , 2016.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…), and ear tissue reactions at each reading control. Unreadable devices were due to either loss or device failure (Carne et al, 2009). When tags were missing, the date was recorded and the animal was re-tagged.…”
Section: Administration and Monitoring Of Identification Devicesmentioning
confidence: 99%